2017
DOI: 10.20944/preprints201707.0026.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modulation of Gut Microbiota of Overweight Mice by Agavins and Their Association with Body Weight Loss

Abstract: Abstract:Agavins consumption has lead to accelerate body weight loss in mice. We investigated the changes on cecal microbiota and short chain fatty acids (SCFA) associated to body weight loss in overweight mice. Firstly, mice were fed with standard (ST5) or high fat (HF5) diet for 5 weeks. Secondly, overweight mice were shifted to standard diet alone (HF-ST10) or supplemented with agavins (HF-ST+A10) or oligofructose (HF-ST+O10), five more weeks. Cecal contents were collected before and after supplementation t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
2
3
1
Order By: Relevance
“…Notably, in Figure S3c,d is clearly Allobaculum much more present in the presence of WPI compared to CAS in non-treated mice. A decrease in Allobaculum was found in obesity-prone mice fed with HFD and an increase of this genera has been linked with a reduction in body weight in obese mice (Huazano-García et al, 2017;Qiao et al, 2014;Ravussin et al, 2012). Furthermore, unlike our previous results (Boscaini et al, 2020), here we observed a decrease in alpha-diversity in HFD-WPI vs HFD-CAS group.…”
Section: F I G U R Econtrasting
confidence: 88%
“…Notably, in Figure S3c,d is clearly Allobaculum much more present in the presence of WPI compared to CAS in non-treated mice. A decrease in Allobaculum was found in obesity-prone mice fed with HFD and an increase of this genera has been linked with a reduction in body weight in obese mice (Huazano-García et al, 2017;Qiao et al, 2014;Ravussin et al, 2012). Furthermore, unlike our previous results (Boscaini et al, 2020), here we observed a decrease in alpha-diversity in HFD-WPI vs HFD-CAS group.…”
Section: F I G U R Econtrasting
confidence: 88%
“…For some diversity indices, such as the number of OTUs and species observed, there was no difference between the NCD and HFD groups, as reported by others. [31][32][33] In the present study, NAC treatment increased the richness and diversity of intestinal bacteria in mice with or without HFD feeding (Fig. S2).…”
Section: Discussionsupporting
confidence: 56%
“…Interaction between MCI001 and Allobaculum may be responsible for metabolic and consequently immune changes in the small intestine of the treated mice which drive the anti-inflammatory response. The observations in this study are reminiscent of the previous data in NOD mice where treatment of obese mice with high fiber diet led to weight loss which was associated with the colonization of Prevotella and Allobaculum ( 56 , 57 ). Allobaculum is one of the high butyrate producing Firmicute and is an active glucose assimilator in the gut ( 58 60 ).…”
Section: Discussionsupporting
confidence: 72%
“…Both Faecalibacterium and Allobaculum are Firmicutes that are butyrate producers and share metabolic similarities in the gut. Both of these bacteria can coexist and dominate in the guts of mice treated for metabolic disorders ( 57 ).…”
Section: Discussionmentioning
confidence: 99%